Emotional Burnout Syndrome among Medical Students in Balochistan: Understanding the Role of Perceived Stress (Journal of Asian Development Studies, 2025)
The current investigation aimed to determine the relationship between Emotional Burnout Syndrome and Perceived Stress among medical students in Balochistan. The study's goal was to investigate the relationship between Emotional Burnout Syndrome and Perceived Stress. It also aimed to explore differences related to Emotional Burnout Syndrome and Perceived Stress concerning various demographics. The data consisted of 75 Medical Students (39 male, 36 female). Convenient sampling was used to select participants with an age range of 18-35 years. For data collection, a cross-sectional survey design was implemented. The Maslach Emotional Burnout Inventory and Perceived Stress Scale were utilised. Pearson Correlation and independent t-test were applied. SPSS 21 cultivated the results. Results revealed significant positive link between Emotional Burnout Syndrome and Perceived Stress. The results also indicated that females reported a higher level of Perceived Stress in comparison to males. At the same time, no significant differences were observed regarding gender in Emotional Burnout Syndrome. The implications of this study extend to both academic and research contexts. It will be beneficial for Medical students` well-being and their academic performance at medical institutional.